Toyotaism Meets the 60-Hour Work Week: Coercion, Consent, and the Regulation of Working Time - Thomas, Mark (Studies in Political Economy, 2007)
Explores the implications of the 2001 revisions to the Employment Standards Act in Ontario, which increased the weekly maximum number of work hours to 60 while loosening the requirements for overtime pay. Based on a case study involving interviews with several workers from the Ontario Toyota plant, the author argues that the changes involve a re-regulation of the labour market that enhances employer-centred flexibility via the construction of a new form of time discipline.